Ribosomal Incorporation of Aromatic Oligoamides as Peptide Sidechain Appendages. (4th February 2020) - Tsiamantas, Christos; Kwon, Sunbum; Rogers, Joseph M.; Douat, Céline; Huc, Ivan; Suga, Hiroaki
Abstract: Derivatives of 4‐aminomethyl‐l ‐phenylalanine with aromatic oligoamide foldamers as sidechain appendages were successfully charged on tRNA by means of flexizymes. Their subsequent incorporation both at the C‐terminus of, and within, peptide sequences by the ribosome, was demonstrated. These results expand the registry of chemical structures tolerated by the ribosome to sidechains significantly larger and more structurally defined than previously demonstrated. Abstract : Erhöhte Toleranz : Das Ribosom toleriert aromatische Oligoamid‐Foldamer/Peptid‐Hybride nicht nur dann, wenn das Foldamer zur Initiierungseinheit gehört, sondern auch, wenn es als Seitenkette im Peptid oder an seinem C‐Terminus gebunden ist. Dies erweitert den bekannten Umfang an Substraten, die vom Ribosom akzeptiert werden, um signifikant größere und strukturell definiertere Substrate.